Dental regenerative therapy: Stem cell transplantation and bioengineered tooth replacement - Kazuhisa Nakao; Takashi Tsuji (Elsevier, 2008)
For clinical treatment of tooth defects and tooth loss, nonbiotechnological approaches, such as the use of prostheses and implants, have generally been employed. Dental regenerative therapies which restore or replace defective teeth using autologous explants are being investigated using current understandings of developmental biology, stem cell biology, and regenerative medicine. Recently, dental tissue stem/progenitor cells, which can differentiate into dental cell lineages, have been identified in both impacted and erupted human teeth, and these cells can be used to regenerate some dental tissues. Tissue engineering using scaffold and cell aggregate methods may also be used to produce bioengineered teeth from dissociated cells for therapeutic applications of whole tooth replacement. Recent breakthroughs in single cell manipulation methods for the reconstitution of bioengineered tooth germ and the investigation of in vivo development of artificial tooth germ in the adult oral environment have been reported. These researches and developments will ultimately lead to the realization of dental regenerative therapies for partial repair by stem cell transplantation and for whole tooth replacement using bioengineered tooth germ.